Pengaruh Knowledge, Skill dan Ability Pimpinan terhadap Kinerja IKM di Kabupaten Pesisir Selatan - Rahmad, Rahmad; Nasfi, Nasfi; Sabri, Sabri (Jurusan PIPS FKIP UMMY Solok, 2019)
The object of this study is IKM Selatan Pesisir Regency, to examine the effect of Knowledge, Skill and Ability of Leaders on Performance in IKM South Pesisir Regency. The purpose of this study is to determine how the model can provide a more precise description of the causality relationship between Knowledge, Skill, Leadership Ability and Performance. The population in this study is the total number of employees in the South Coastal District IKM with a total of 1,656 employees. With a sample of 100 people taken from a number of business units engaged in manufacturing such as the production of handicrafts, food, bags, shoes, crackers, garments and so on at IKM South Coastal District. Analysis of the research data used is the structural equation model with the SPSS application program to test 4 (two) hypotheses that have been developed, the hypothesized relationship is a causal relationship. And the results of the hypothesis show that 4 (two) proposed hypotheses are accepted. The significance value of the Knowledge variable (X1) is 0.031, the significance value of the Skill variable (X2) is 0.028 and the significance value of the Ability variable (X3) is 0.046, it is evident that if the significance value (sig) or probAbility value (probAbility) smaller than the significant level used (= 0.05), it can be concluded that there is a significant influence of the variables Knowledge (X1), Skill (X2) and Ability (X3) on Performance in IKM South Coastal District.